Strategi Pemanfaatan Kearifan Lokal dalam Pengembangan Desa Wisata Pandean Kabupaten Trenggalek - Moh. Musleh; Nabila Septia Rosa (Journal of Contemporary Public Administration, 2024)
The term tourist village is closely related to Pandean. The reason is, this area is quite an attraction for local tourists. This research aims to identify strategies for utilizing local wisdom in developing the Pandean Tourism Village, Trenggalek Regency. The urgency of this research is to increase tourism potential, what needs to be done is to plan tourism development using the 3A concept (attractions, facilities and accessibility) which is a requirement in developing a tourist destination, because these three elements have an important role. In building a comfortable travel experience and meeting tourist needs. This research uses a descriptive qualitative approach, namely providing a systematic, factual and accurate description of the facts and potential of tourism in the Pandean Tourism Village. The location of this research is in Dongko District, Trenggalek Regency, East Java Province, while the location in this research is Pandean Tourism Village. Data collection techniques use observation, documentation and interviews. The informants in this research were: 1) Dewi Arum Pulosari Tourism Awareness Group; 2) Head of Pandean Village; and 3) business actors in the Pandean Tourism Village. The results of this research indicate that the Pandean Tourism Village is not yet optimal in implementing the 3A tourism concept. Various interesting tourist attractions are presented at Pandean Tourism Village to make an impression on visitors. The accessibility of the Pandean Tourism Village does not provide comfort for tourists, the road conditions are not good, large buses cannot enter the Pandean Tourism Village location because the road conditions are narrow. Existing facilities in the Pandean Tourism Village need to be developed, so that they can meet the needs of visiting tourists.